DEEP LEARNING BASED APPROACH FOR BIRD SPECIES IDENTIFICATION AND CLASSIFICATION (International Journal of Food and Nutritional Sciences, 2024)
Ornithologists and ecologists often face challenges with manual bird species identification, which can be time-consuming and prone to errors. Traditional methods like field guides and acoustic monitoring have limitations, including subjective visual identification and limited acoustic data coverage. These methods can be difficult for non-experts and fail to provide real-time insights into bird populations. To address these issues, we introduce a state-of-the-art deep learning approach that uses neural networks to automatically identify and classify bird species based on visual and acoustic cues. Conventional methods rely on user expertise and can result in misclassifications due to variability in bird plumage and seasonal changes. Acoustic monitoring systems also require expert interpretation and may overlook visual cues. Our Deep Learning-based Approach for Bird Species Identification and Classification employs Convolutional Neural Networks (CNNs) to process visual and acoustic data. By using large, labeled datasets of bird images and audio recordings, our system can recognize and classify bird species accurately, accounting for seasonal variations. Additionally, our system supports real-time monitoring via mobile applications and field-deployable hardware, providing instant insights into bird populations. This automated approach enhances the efficiency and accuracy of bird identification, aiding in the understanding of avian ecosystems and conservation efforts.